Condom use increased after a peer group intervention implemented by community volunteers in Malawi - Kathleen F. Norr; Chimwemwe K. Banda; Cecilia Chang; Shruthi Krishna; Lily C. Kumbani; Li Liu; Linda L. McCreary; Crystal L. Patil (BMC, 2024)
Abstract Background HIV prevention remains a global priority, especially in sub-Saharan Africa. Our research team previously developed an evidence-based peer group program for HIV prevention called Mzake ndi Mzake (Friend to Friend). A community-engaged collaboration adapted the program for community ownership and implementation. Here we report whether this HIV prevention program, implemented by community volunteers, increased condom use among sexually active individuals in rural Malawi. Methods Three communities sequentially rolled out the program. Effectiveness was evaluated using a stepped wedge design. Repeated surveys 11-13 months apart were conducted between 2016 and 2019. At Time 1, no community had offered the intervention. At Time 2, the first community had offered the intervention and two had not (control group). At Time 3, two communities had offered the intervention and one had not (control group). We used two condom use indicators; condom use frequency in the last 2 months (N = 771) and condom use at last sex (N = 880). The analytical sample included all sexually active persons answering that question at one or more time points. Mixed-effects cumulative logit and Generalized Estimating Equation (GEE) models were used to model the two condom indicators over time, controlling for demographic factors, UNAIDS HIV knowledge, safer sex self-efficacy and partner communication. Results This peer group intervention implemented by trained community volunteers increased both condom use indicators at Times 2 and 3. In the final adjusted models with non-significant factors removed, condom use in the last two months increased for the intervention group vs. control group [Time 2: Adjusted Odds Ratio (AOR) = 1.59 (1.15, 2.21); Time 3: AOR 2.01 (1.23, 3.30)]. Similarly, condom use at last sex increased for the intervention group vs. control group [Time 2: AOR = 1.48 (1.08, 2.03); Time 3: AOR 1.81 (1.13, 2.90)]. Other significant predictors of greater condom use were also described. Although the intervention increased UNAIDS HIV knowledge, knowledge did not predict condom use. Conclusions In this community-engaged implementation study, an evidence-based peer group program for HIV prevention increased condom use when delivered by trained community volunteers. Community ownership and program delivery by trained volunteers offer an innovative and cost-effective strategy to address ongoing HIV prevention needs without overburdening healthcare systems in sub-Saharan Africa. Trial registration Clinical Trials.gov NCT02765659 Registered May 6, 2016.